Exploring Impact of Quality Accreditation on Students’ Interests in Islamic Higher Education - Agus Yudiawan (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2020)
This study aims to map and analyze students’ interests before and after study program accreditation, the effect of accreditation grade, and attempt to increase the value of accreditation. This study employed a mixed-methods approach with a sample of 218 participants for quantitative data and ten informants for qualitative data. The data were collected by using interviews, focus group discussion, observation, and questionnaires. To analyze the data, triangulation is performed to display the frequency distribution, and simple regression analysis is also carried out to find the data related to the effect of the accreditation. Study results expose that firstly, there was a significant improvement in the students’ interest after study program accreditation with an average of 87.5%. Secondly, the accreditation grade gave a positive and significant effect on students’ interest in choosing study programs at a public Islamic university in West Papua, Indonesia. Lastly, there were several endeavors taken into account to increase accreditation score, i.e. synergizing an integrated internal quality assurance system, having an acceleration program for students’ length of study, digitizing students’ admission system, enhancing digital-based learning models, and increasing lecturers’ competence in academic writing, community service, and publication. The present study suggests that the quality of study program accreditation should be a pivotal concern in organizing Islamic higher education